Effect of net voltage of thermoelectric generator on performance of hybrid energy device. (November 2020) - Park, Yoonbeom; Cho, Kyoungah; Yang, Seunggen; Park, Taeho; Park, Sungeun; Song, Hee-eun; Kim, Soo Min; Kim, Sangsig
Abstract: In this study, we investigate the performance of a hybrid energy device (HED) composed of a photovoltaic cell (PVC) and a thermoelectric generator (TEG) through an analysis of the voltage difference (net voltage) between voltage drop and thermoelectric voltage. The efficiency of the HED is compared with that of an isolated PVC at irradiances in the range of 200 ∼ 1000 W/m 2 . At an irradiance of 200 W/m 2, the maximum power of the HED is 6.7% higher than that of the isolated PVC because the thermoelectric voltage is greater than the voltage drop in the TEG. Our study reveals that the net voltage between the voltage drop and the thermoelectric voltage determines whether the output power of the HED is higher than that of the isolated PVC. In addition, the relationship between the net voltage and the increase in maximum power of the HED reveals that the net voltage becomes a predictor of the performance of HED.